Prevalence of Non-Tuberculosis Mycobacterial Infections among Tuberculosis Suspects in Iran: Systematic Review and Meta-Analysis - Nasiri, Mohammad Javad; Dabiri, Hossein; Darban-Sarokhalil, Davood; Hashemi Shahraki, Abdolrazagh (PloS one, 2015)
The infections due to Non-Tuberculosis Mycobacteria (NTM) are becoming an important health problem in many countries in the world. Globally, an increase in NTM infections has been reported from many countries around the world. However, limited information is available about the prevalence of NTM infections in Iran. The data of the prevalence of NTM infections were collected from databases such as PubMed, Web of science, Cochrane Library, Embase, Scopus, Iranmedex, and Scientific Information Database. Comprehensive Meta-Analysis (V2.0, Biostat) software was used to analyze the data. The meta-analyses showed that the prevalence of NTM infections was 10.2% (95% confidence interval [95% CI] 6.3-15.9) among culture-positive cases of tuberculosis (TB) in Iran. The further stratified analyses indicated that the prevalence of NTM was higher in studies that were done after year 2000. Additionally, M. simiae (43.3% [95% CI 36.8-50.0]), M. intracellucar (27.3% [95% CI 0.7-95.5]) and M. fortuitum (22.7% [95% CI 16.1-30.9]) were the most prevalent NTM species, respectively. The relatively high prevalence of NTM infections (10.2%) among culture positive cases for TB underlines the need for greater enforcement of infection control strategies. Establishment of appropriate diagnostic criteria and management guidelines for NTM diseases and expanding the number and quality of regional reference laboratories may facilitate more accurate action for prevention and control of NTM infections in Iran.